'Where chaos was, there shall be a matrix' (de Maré). The large analytic group between chaos and creativity—reflections on the concept, its history and further evolution. (March 2021) - Potthoff, Peter
The author presents a survey of the development of large group theory. Older publications (e.g. Kreeger, Turqet, also drawing on Freud, M. Klein, Bion) describe the chaotic-aggressive, near-psychosis character of the large group, a certain contrast between the seemingly 'benign' small group and the 'destructive' large group and a predominantly dyadic relationship between the conductor and the large group. More recent publications (Wilke, Island, formerly also de Maré) underline the creative-constructive potential of the large group and the intersubjective interweaving of the conductor and the large group. Experiences with a conductor-pair in the daily large group of the Altaussee workshop instead of one conductor are discussed. The author pleads for the application of modern intersubjective theorizing to the large group. The analytic attitude and intervention technique would be changed: the traditional position of strict neutrality, anonymity and abstinence as well as the emphasis on whole-group interpretations would be substituted by a more open stance that does not hide the subjectivity of the conductor(s) but rather reveals and uses the conductor's subjectivity to promote the analytic process.